Pengembangan Sistem Informasi Pengelolaan Praktik Industri Terintegrasi Sistem Informasi Akademik Terpadu Universitas Negeri Surabaya - Putra, Ricky Eka; Asmunin, Asmunin (INTEGER: Journal of Information Technology, 2021)
Praktik Industri (PI) is one of the mandatory courses that must be taken by students of all majors within the Faculty of Engineering, State University of Surabaya. Through this course, students are required to carry out learning in institutions/companies according to the field of science with the aim of knowing and practicing what they have learned in real practice in the company. The main problem in implementing PI is that all administrative processes are not integrated so that it is difficult for the parties involved in managing the PI. Some examples of problems related to PI include student information and industrial premises, activities while in industry, students who have not done PI, PI guidance notes, notes related to PI exams, Student Information and Advisory Lecturers, administrative data related to PI, Feedback from Industry and others. -other. Based on these problems, PI activities require an PI management information system that is integrated with the Integrated Academic Information System (SIAKADU) in the Department of Informatics, Faculty of Engineering Unesa. This PI management information system is built on a web-based basis using open source technology and is integrated with data on SIAKADU.